Alcohol consumption and the risk of liver disease: a nationwide, population-based study - Moon, Sang Yi; Son, Minkook; Kang, Yeo Wool; Koh, Myeongseok; Lee, Jong Yoon; Baek, Yang Hyun (Frontiers in Medicine, 2023)
Although most patients with alcohol-related liver disease (ALD) have a history of prolonged and heavy drinking, there is no clear threshold defining the level of alcohol consumption that leads to ALD. We aimed to evaluate the correlation between average alcohol consumption and the risk of liver disease and to determine the threshold for clinically significant alcohol consumption.Using the Korean National Health Insurance database, we identified participants who underwent a health-screening program in 2010 and 2011 and retrospectively analyzed their data until 2019. To diagnose and categorize the extracted participants, we used the International Classification of Diseases version 10 and Fatty Liver Index. The primary outcome was to determine the incidence of newly diagnosed liver-related diseases during the observation period and compare the incidence of liver-related diseases among non-drinkers and drinkers based on the amount of alcohol consumption.A total of 53,006 patients were enrolled and followed-up for a median of 8.4 years, during which 1,509 cases of liver-related diseases occurred. The participants were divided into five groups: no alcohol consumption (n = 31,359), 1st quartile (n = 5,242), 2nd quartile (n = 5,704), 3rd quartile (n = 5,337), and 4th quartile (n = 5,364). The corresponding number of glasses of alcohol consumed per week for each quantile (Q1, Q2, Q3, and Q4) was labeled 2.5 ± 1.1 standard units (1 standard unit = 8 g alcohol), 5.4 ± 1.9 standard units, 11.5 ± 3.3 standard units, and 27.9 ± 18.2 standard units, respectively. Compared with non-drinkers, the risk of liver-related disease was found to be higher in Q1 drinkers (adjusted hazard ratio [aHR], 1.09; 95% CI, 0.90-1.33), Q2 drinkers (aHR, 1. 10; 95% CI, Q3 drinkers (aHR, 1.33; 95% CI, and Q4 drinkers (aHR, 1.47; 95% CI,.We report that our study has shown that drinking more than 11.5 ± 3.3 standard units/week (92 ± 26.4 g/week) significantly increases the risk of developing liver-related diseases. Therefore, as a preventive measure to reduce the risk of developing liver disease, alcohol consumption should be limited beyond traditionally recommended levels.